Case Report of Sporadic Type of Medullary Thyroid Carcinoma - Bitoska, Iskra; Todorova, Biljana; Jovanovska Mishevska, Sasha; Plasheski, Tosho; Stojovska jovanovska, Elizabeta; Stojkoska, E (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2022)
Background: Medullary thyroid carcinoma (MTC) constitutes around 5% of all thyroid cancers and it usually arises from parafollicular C-cells. Both sporadic and familial forms are seen. The prognosis of MTC is worse in comparison to other differentiated thyroid cancers. Hereby, we present the case report of one patient with sporadic MTC. Case Report: We present a 67-years-old male with presence of one dominant hypoechoic nodule in the right lobe (4x3x5cm) on thyroid ultrasonography. Fine-needle aspiration biopsy (FNAB) of the right lobe was done twice in a 10 months period, with no malign cells discovered. Three months after the second FNAB, scan with Technicium 99 was done, which showed ‘cold zone’ in the middle of the right thyroid lobe. Computer Tomography (CT) of the neck revealed cystic lesion in the same thyroid lobe. The patient underwent right lobectomy. The final histopathological finding was MTC: pTNM = pT1 pNx pMx G2 Cx. After getting the results, additional surgery was done and this time the total right lobe thyroidectomy was performed. Conclusion: MTC can occur as sporadic, as well as genetic disease. We showed that this case of MTC was a sporadic type on account of absence of family history, normal plasma and urinary catecholamine levels, negative genetic testing for mutations in RET, normal CT scan of abdomen and normal Cromogranin
Keywords: medullary thyroid carcinoma; multiple endocrine neoplasia; thyroid nodus